DATA MINING SYSTEM IMPLEMENTATION BY GROUPING SALES AT PT. GANDATAMA CROWN - manullang, sehat saorasi; Palma Juanta (INFOKUM, 2022)
This research discusses how to classify the data from period to period by implementing the Apriori method. The data used in this research is sales in 2021-2022. Researchers have carried out stem analysis using the a priori data method used in February 2021. This system can classify sales according to the type of goods that consumers are more interested in. So the types of sales items that are included in the best-selling sales pattern are, 40%, 60%, 70%.